Meanings and Expressions of Caring among Nurses in Clinical Workplace: A Literature Review - Mayasari, Putri; Hatthakit, Urai; Thiangchanya, Pratyanan (Department of Nursing, Faculty of Medicine, Diponegoro University, 2013)
Background: Research shows that nurse retention is high as a result of a stressful work environment coupled with inadequate support in clinical workplace. Caring among nurses is therefore crucial in enhanced and enriched the working environment that helps increase nurse’s satisfaction and retention in the profession.Purpose: To explore the meanings and expressions of caring among nurses in clinical workplace.Methods: Literature review of existing articles on electronic databases was conducted. The meanings and expressions of caring among nurses were identified. The year of publication ranged from 2000-2012.Result: Based on inclusion criteria, 10 articles reviewed were included. There was very limited result describing meanings of caring among nurses. However, caring expressions had been identified and categorized into personal and professional levels. There were some common themes such as caring through helping and support, caring through appreciating, and acknowledging unappreciated caring.Conclusion: Caring among nurses is very important to keep nurses emerged and able to work more effectively. However, caring varies within cultures and there are still limited studies among nurses in nonwestern society. Therefore, further research is needed to describe meanings and expressions of caring in clinical workplace that is beneficial in enhancing caring environment, increasing nurse’s satisfaction and nurse retention.Keyword: caring among nurses, meaning of caring, caring expressions, clinical work.